Psychological Dimensions in Yousef Bar Yousef’s Plays - Ammar Mohammed Hattab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Since the studies of modern psychology emerged by Freud, his discovery of the unconscious world, science is affected by this trend, especially dramatic literature specializing in the field of dramatic writing; for its influence by psychology, it is based on addressing the human soul through the theatrical personality and what feels of emotion and passion. However, most of the arts, which is theater, has approached from the psychological literary studies of all his kinds and directions. And the criticism and modern style based on these studies and accompanying the development of modern psychological research methods, In this area, psychological criticism appeared in studies and modern psychological theories which developed by the school of psychoanalysis scholars as Freud and his students after him. The emergence of these psychological studies has preceded by the emergence of a group of creative literary products, it carries in its artistic nature a psychological trend based on psychological foundations and the views of modern psychology, whether intended or unintended, it was the play, it has concerned with highlighting the lifestyle of its mental and sentimental characters, rather than her interest in creating plot and dramatic movement in it. There plays have based on the new trend that emerged in the beginning of the twentieth century which is the sentiment or consciousness trend, invented by the French novelist de Jardin and it was later developed by James Joyce and Virginia Woolf. This trend of consciousness and sentiment studies can be used to analyze theatrical works, especially in the Jewish theater. It is a field of study, especially on the texts of the author (Yousef Bar Yousef) who committed this type of plays to disclose the mysteries of the hearts of his characters, and what is going on in themselves including secrets and psychological problems. This research, ( Psychological Dimensions in Yousef Bar Yousef’s Plays, ) aims to analyze the plays of Yousef Bar Yousef psychologically according to the psychological approach. It is based on the facts of modern psychology and its psychological explanations for the behavior of human characters. The Critics of this trend tried to apply these theories to the souls of theatrical characters. In their analysis, they found the pathological psychological problems in the theatrical characters. Furthermore, they have analyze the souls and qualities of their authors, being the first factor in the existence of these characters. The study concluded by mentioning the most prominent results that led to it